2020
DOI: 10.1039/c9cc09411c
|View full text |Cite
|
Sign up to set email alerts
|

One-pot aerobic oxidative sulfonamidation of aromatic thiols with ammonia by a dual-functional β-MnO2 nanocatalyst

Abstract: High-surface-area β-MnO2 nanoparticles exhibited high activity for the one-pot oxidative sulfonamidation of thiols to sulfonamides using O2 and NH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…In contrast to those on α, γ, ε, and δ-MnO 2 , ,,, studies on the controlled synthesis of β-MnO 2 with a high surface area have still been limited because the activation barrier for the transformation of other manganese oxides to β-MnO 2 has been reported to be high, although β-MnO 2 is a thermodynamically stable phase among the MnO 2 polymorphs. ,, Therefore, the hydrothermal synthesis of β-MnO 2 typically requires high reaction temperatures (150–180 °C) or long reaction times (12–48 h), which result in a significant increase in the β-MnO 2 particle size and low surface areas (3–35 m 2 g –1 ). ,,,, In contrast, soft- and hard-template methods for the synthesis of mesoporous β-MnO 2 materials with high surface areas (68–195 m 2 g –1 ) have been reported, despite the need for multistep procedures or the utilization of organic and inorganic templates or organic reductants. ,, During the course of our investigations on catalytic biomass conversion and aerobic oxidation, we have recently reported that β-MnO 2 can act as the most effective oxidation catalyst for the aerobic oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) as a bioplastic monomer on the basis of combined computational and experimental studies . The successful synthesis of the high-surface-area β-MnO 2 nanoparticles by the simple calcination of precursors prepared from NaMnO 4 and MnSO 4 at 400 °C has resulted in significant improvement of the catalytic performance in comparison with β-MnO 2 synthesized under hydrothermal conditions ( β - MnO 2 - HT ) (Figures and S1).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to those on α, γ, ε, and δ-MnO 2 , ,,, studies on the controlled synthesis of β-MnO 2 with a high surface area have still been limited because the activation barrier for the transformation of other manganese oxides to β-MnO 2 has been reported to be high, although β-MnO 2 is a thermodynamically stable phase among the MnO 2 polymorphs. ,, Therefore, the hydrothermal synthesis of β-MnO 2 typically requires high reaction temperatures (150–180 °C) or long reaction times (12–48 h), which result in a significant increase in the β-MnO 2 particle size and low surface areas (3–35 m 2 g –1 ). ,,,, In contrast, soft- and hard-template methods for the synthesis of mesoporous β-MnO 2 materials with high surface areas (68–195 m 2 g –1 ) have been reported, despite the need for multistep procedures or the utilization of organic and inorganic templates or organic reductants. ,, During the course of our investigations on catalytic biomass conversion and aerobic oxidation, we have recently reported that β-MnO 2 can act as the most effective oxidation catalyst for the aerobic oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) as a bioplastic monomer on the basis of combined computational and experimental studies . The successful synthesis of the high-surface-area β-MnO 2 nanoparticles by the simple calcination of precursors prepared from NaMnO 4 and MnSO 4 at 400 °C has resulted in significant improvement of the catalytic performance in comparison with β-MnO 2 synthesized under hydrothermal conditions ( β - MnO 2 - HT ) (Figures and S1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have focused on the liquid-phase catalysis of hexagonal perovskites with unique face-sharing octahedral units based on high valency metal species. During the course of our investigation on crystalline first-row metal oxide catalysts, [12][13][14][15][16][17] we have successfully synthesized various hexagonal perovskite nanoparticle catalysts for the liquid phase selective oxidation of various organic substrates with O 2 as the sole oxidant. [15][16][17] In particular, high valency iron-containing BaFeO 3−δ was found to act as an efficient heterogeneous catalyst for the aerobic oxidation of alkanes to the corresponding alcohols and ketones, in sharp contrast to Fe 3+ /Fe 2+ oxides.…”
mentioning
confidence: 99%
“…Very recently, the research group of Kamata and Hara explored the catalytic application of dual-functional high-surface-area β-MnO 2 (β-MnO 2 -HS) nanoparticles for the direct sulfonylation of ammonia with thiols to synthesize primary sulfonamides. 43 Various aromatic and heteroaromatic thiols 39 have been reacted with aqueous NH 3 in the presence of a catalytic amount of β-MnO 2 -HS under O 2 atmosphere to give (hetero)aryl sulfonamides 40 in moderate to high yields ( Scheme 21 ). The reaction works better with electron rich than with electron poor substituents on the aryl thiols (88% yield for 4-OMe-substituted substrate compared to 58% for the 4-nitro derivative).…”
Section: Synthesis Of Sulfonamidesmentioning
confidence: 99%